Salmon Calcitonin Attenuates Some Behavioural Responses to Nicotine in Male Mice - Aranäs, Cajsa; Vestlund, Jesper; Witley, Sarah; Edvardsson, Christian E.; Kalafateli, Aimilia Lydia; Jerlhag, Elisabet (Frontiers in Pharmacology, 2021)
The behavioural responses to nicotine involve appetite-regulatory hormones; however, the effects of the anorexigenic hormone amylin on reward-related behaviours induced by nicotine remain to be established. Previous studies have shown that the amylinergic pathway regulates behavioural responses to alcohol, amphetamine and cocaine. Here, we evaluated the effects of salmon calcitonin (sCT), an amylin and calcitonin receptor (CTR) agonist, on nicotine-induced locomotor stimulation and sensitisation as well as dopamine release in the nucleus accumbens (NAc) shell. Moreover, we investigated the effects of sCT on the acquisition and expression of nicotine-induced reward in the conditioned place preference (CPP) paradigm. Finally, we performed Western Blot experiments in an attempt to identify the levels of the amylin receptor components CTRa, CTRb, and RAMP1 in reward-related areas of mice responding differently to repeated injections of sCT and nicotine in the locomotor sensitisation test. We found that sCT blocked nicotine’s stimulatory and dopamine-releasing effects and prevented its ability to cause locomotor sensitisation. On the other hand, sCT did not alter nicotine-induced acquisition and expression of CPP. Lastly, sCT-nicotine treated mice from the locomotor sensitisation experiment displayed higher levels of total CTR, i.e. CTRa and CTRb together, in the reward-processing laterodorsal tegmental area (LDTg) of the brain compared to mice treated with vehicle-nicotine. Overall, the present data reveal that activation of CTR or/and amylin receptors attenuates certain nicotine-induced behaviours in male mice, further contributing to the understanding of appetite-regulatory peptides in reward regulation.